2005
DOI: 10.2225/vol8-issue2-fulltext-11
|View full text |Cite
|
Sign up to set email alerts
|

Continuous citric acid secretion by a high specific pH dependent active transport system in yeast Candida oleophila ATCC 20177

Abstract: The pH influence on continuous citric acid secretion was investigated in Candida oleophila ATCC 20177 (var.) under NH 4 + limiting state steady conditions, using glucose. Highest citric acid concentration of 57.8 g/l, citrate/isocitrate ratio of 15.6, space-time yield of 0.96 g/(l x hr) and biomass specific productivity of 0.041 g/(g x hr) were obtained at pH 5 and 60 hrs residence time. Only 22.8 g/l (39.4%) and a ratio of 9.9 were achieved at pH 6 pH and 12.4 g/l (21.5%) and a ratio of 3.7 at pH 3. Under non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
4
27
1
Order By: Relevance
“…C. oleophila or Y. lipolytica strains have been shown capable of producing noticeable citric acid quantities after nitrogen exhaustion during growth on glucose or similarly metabolized substrates (e.g. glycerol) as secondary anabolic activity in several fermentation configurations 11, 23, 36, 41–44. The culture conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…C. oleophila or Y. lipolytica strains have been shown capable of producing noticeable citric acid quantities after nitrogen exhaustion during growth on glucose or similarly metabolized substrates (e.g. glycerol) as secondary anabolic activity in several fermentation configurations 11, 23, 36, 41–44. The culture conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in all fermentations, a remarkable drop of the culture medium pH was observed, suggesting accumulation of organic acids into the culture medium. The pH was always maintained within the range 5.2-6.2, since in previous investigations it had been demonstrated that the maintenance of pH in this range was as a very important factor for the success of the fermentation [28,33]. Cit was the major organic acid accumulated into the culture medium, while other organic acids (e. g., a-ketoglutaric, acetic, pyruvic acid) were produced in negligible quantities (sum of organic acids produced was around 10% of Cit).…”
Section: Kinetics In Nitrogen-limited Media With Initial Glucose At 3mentioning
confidence: 99%
“…The bioprocess has also been successfully simulated and optimized with the aid of various models [6,11,12,[25][26][27]. Production of extracellular citric acid or intracellular lipid when sugars or similarly metabolized compounds are used as the sole substrate are, in their first steps, biochemically identical, and occur after intracellular nitrogen exhaustion [21][22][23]28]. The only difference in these processes is in the level of the enzyme ATP-citrate lyase, which catalyzes the cleavage of intracellular citric acid into oxaloacetate and acetyl-CoA, the latter being used as base-unit for the synthesis of intracellular fatty acids, by a quasi-inverted b-oxidation process [21,22,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that below pH 5, citric acid production decreases and accumulation of other products like erythritol, arabitol and mannitol is favoured. Transport of citrate across cell membrane is also affected (Anastasisdis & Rehm, 2005;Karasu, Yalcin, Bozdemir & Ozhas, 2010).…”
Section: Microbial Strainsmentioning
confidence: 99%